Sentiment Analysis of Merdeka Belajar-Kampus Merdeka Program on Twitter Using the Naive Bayes Algorithm - Arthana, I Made Teguh; Andreyana, Putu Veda; Fauzi, Muhammad (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2023)
Merdeka Belajar-Kampus Merdeka (MBKM) is a learning model in higher education that provides freedom and flexibility to students. This model aims to create a culture of creativity, innovation, and non-restriction by allowing students to study for three semesters outside their study programs. The program is an initiative of the Ministry of Education and Culture of the Republic of Indonesia in response to the impact of the Covid-19 pandemic. However, the MBKM program has received varied responses from the public, especially from students who have experienced its effects and hold different views on the MBKM policy. As this is a new policy, it is important to conduct analysis and evaluation of this program involving feedback from the community to enhance its performance. In a research on sentiment analysis of the Merdeka Belajar program on Twitter using the Naïve Bayes algorithm gets an accuracy value of 78% of the model to be able to predict positive, negative, and neutral classes from the 203 testing data used or 20% of all data (1015 data).